iMEC-APCOMS 2019 the best platform to exhibit industry and manufacturing engineering research product - Nurrina, Rosli (2019)
Faculty of Manufacturing and Mechatronics Engineering Technology (FTKPM) has successfully organized the 4th International Manufacturing Engineering Conference (iMEC) 2019 on 21st to 22nd August 2019 at The Everly Hotel, Putrajaya, Malaysia.